The names of districts and housing estates in Tomaszów Mazowiecki - Pacan-Bonarek, Lidia (Geographical names in physical space, 2016)
The article entitled The names of districts and housing estates in Tomaszów Mazowiecki is an attempt to complete the works and studies on city names in Poland. The analysis of proper names material was based on the meaning and formal names classification which allowed to separate the topographic names (Białobrzegi, Babi Dół), the cultural names (Baraki, Hubala housing estate), the possessive names (Cekanów), the ethnic names (Nagórzyce), the family names (Rawitów), the patronymic names (Starzyce), the relational names (Karpaty, Nowy Port) and the double meaning names (Gustek, Piekło). In each of the types one tried to separate the motivated names and unmoti vated names, and synthetic names and analytic names, if they occurred. The most popular types of urbanonyms which occurred in the discussed area are the relational, topographic and cultural names. The application of semantic classification allowed to emphasise the relation between toponyms and land configuration, material and spiritual culture of the society of this region. Just like in the example of other cities the oldest group of city names of Tomaszów Mazowiecki are the district names which at the beginning had been the names of the villages and hamlets. When the towns developed the villages were absorbed by them.